Perspective on the Use of Universal Language (English) for Modern Retail Employees to Recognize Goods - Sibuea, Parulian; Yahya, Nazar Alwi; Hasibuan, Jihan Amanda (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
The use of product language, whether in the form of labels, advertising, or packaging, plays an important role in attracting consumers attention and influencing their purchasing decisions. The aim of this research is to analyze how language is used in everyday consumer product contexts and its impact on consumer perceptions and behavior. This research uses a qualitative approach using content analysis techniques on various products circulating in the Indonesian market. Research shows that the use of persuasive and informative language on labels and packaging increases product appeal and strengthens the brand image in the eyes of consumers.In addition, the language used in advertising has proven to be effective in building trust and increasing consumer loyalty. This research concludes that the use of appropriate and strategic language in products is one of the key factors in marketing that influences the success of a product in the market